Transmission and Toxigenic Potential of Vibrio cholerae in Hilsha Fish (Tenualosa ilisha) for Human Consumption in Bangladesh - Hossain, Zenat Z.; Farhana, Israt; Tulsiani, Suhella M.; Begum, Anowara; Jensen, Peter K. M. (Frontiers in Microbiology, 2018)
Fish have been considered natural reservoirs of Vibrio cholerae, the deadly diarrheal pathogen. However, little is known about the role of fish in the transmission of V. cholerae from the Bay of Bengal to the households of rural and urban Bangladesh. This study analyzes the incidence and pathogenic potential of V. cholerae in Hilsha (Tenualosa ilisha), a commonly caught and consumed fish that exhibits a life cycle in both freshwater and marine environments in Bangladesh. During the period from October 2014 to October 2015, samples from the gills, recta, intestines, and scale swabs of a total of 48 fish were analyzed. The fish were collected both at local markets in the capital city Dhaka and directly from fishermen at the river. PCR analysis by targeting V. cholerae species-specific ompW gene revealed that 39 of 48 (81%) fish were positive in at least one of the sample types. Real-time PCR analysis demonstrated that the cholera-causing ctxA gene was detected in 20% (8 of 39) of V. cholerae-positive fish. A total of 158 V. cholerae isolates were obtained which were categorized into 35 genotypic groups. Altogether, 25 O1 and 133 non-O1/O139 strains were isolated, which were negative for the cholera toxin gene. Other pathogenic genes such as stn/sto, hlyA, chxA, SXT, rtxC, and HA-P were detected. The type three secretion system gene cluster (TTSS) was present in 18% (24 of 133) of non-O1/O139 isolates. The antibiotic susceptibility test revealed that the isolates conferred high resistance to sulfamethoxazole-trimethoprim and kanamycin. Both O1 and non-O1/O139 strains were able to accumulate fluid in rabbit ileal loops and caused distinctive cell death in HeLa cell. Multilocus sequence typing (MLST) showed clonal diversity among fish isolates with pandemic clones. Our data suggest a high prevalence of V. cholerae in Hilsha fish, which indicates that this fish could serve as a potential vehicle for V. cholerae transmission. Moreover, the indigenous V. cholerae strains isolated from Hilsha fish possess considerable virulence potential despite being quite diverse from current epidemic strains. This represents the first study of the population structure of V. cholerae associated with fish in Bangladesh.